2013
DOI: 10.4081/hpr.2013.e22
|View full text |Cite
|
Sign up to set email alerts
|

Psychological barriers and facilitators of colorectal cancer screening: a French qualitative study

Abstract: The aim of this qualitative study was to explore the psychological barriers to and facilitators of undergoing the Hemoccult-II® colorectal cancer screening test in France. Sixty-nine French people aged 50 to 74 years were divided into seven qualitative focus groups. Three issues were discussed with participants: knowledge and beliefs about colorectal cancer screening; facilitators of colorectal cancer screening by Hemoccult-II®; barriers to colorectal cancer screening by Hemoccult-II®. All the discussions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
3
2
0
Order By: Relevance
“…Another study has shown that non-adherence is not caused by a difficulty related to performing the test, as the participants generally considered the test to be relatively simple to perform with no particular problems, at least compared with other similar types of medical procedures. This finding confirms the results of several authors who reported that this type of test is convenient and relatively simple to use (Bridou et al, 2013). Although most countries in Europe currently use the immunological test, the reasons for longitudinal adherence to colorectal cancer screening are common for both immunological and guaiac tests.…”
Section: Relaxation Effect After a Negative Results In Fobtsupporting
confidence: 89%
See 1 more Smart Citation
“…Another study has shown that non-adherence is not caused by a difficulty related to performing the test, as the participants generally considered the test to be relatively simple to perform with no particular problems, at least compared with other similar types of medical procedures. This finding confirms the results of several authors who reported that this type of test is convenient and relatively simple to use (Bridou et al, 2013). Although most countries in Europe currently use the immunological test, the reasons for longitudinal adherence to colorectal cancer screening are common for both immunological and guaiac tests.…”
Section: Relaxation Effect After a Negative Results In Fobtsupporting
confidence: 89%
“…However, most studies highlight the lack of information and media interest in CRC screening, with more focus on the difficulty of discussing CRC screening with other individuals because it is considered a shameful subject (Beeker et al, 2000;Bridou et al, 2013).…”
Section: Lack Of Comprehensionmentioning
confidence: 99%
“…As per the HBM, the perceived benefits outweighed their perceived barriers to obtaining a screening [ 24 ]. These findings are consistent with the findings of other French studies [ 33 , 39 ].…”
Section: Discussionsupporting
confidence: 94%
“…As predicted by the Health Belief Model, the participants who perceived that they were susceptible to cancer and realized the seriousness of the disease and its consequences, expressed more motivation to get screened [ 24 ]. Similar to our study’s findings, Bridou et al‘s study [ 33 ] revealed that the main psychological facilitators of colorectal screening included having information about colorectal cancer screening and individuals’ perception of risk to getting colorectal cancer. Moreover, a systematic review conducted by Honein-AbouHaidar et al [ 34 ], demonstrated that the decision to participate in colorectal cancer screening depended on an individual’s awareness of colorectal cancer screening; increased awareness contributed to higher motivation for screening.…”
Section: Discussionsupporting
confidence: 91%
“…This confirms previous findings that psychological barriers may prevent colorectal cancer screening. [ 9 10 ] These fears and misconceptions can be addressed through targeted educational interventions and healthcare provider reassurance to increase screening participation. Participants’ colorectal cancer information sources were also examined.…”
Section: Discussionmentioning
confidence: 99%